Effect of Soil Conditioning on Soil Penetration Resistance and Traction Power Demand of Ploughing - Tuba Géza (Sciendo, 2021)
Soil compaction and degradation due to improper tillage are problems involving significant natural and economic damages. On compacted soils, suitable cultivation can be implemented only with higher energy and traction force input. In our study, the effect of a soil conditioner (Neosol) was examined on the penetration resistance of the soil and the traction power demand for ploughing in the experiment set up in the East-Slovak Plain in 2017 ‒ 2018 to justify several preliminary results showing that long-term soil conditioning results in enhanced root system, improved soil structure, cultivability, water- and salt regime. We found a positive effect of Neosol application with both investigated parameters and its long-term effect was also justified. The penetration resistance values of the soil of the untreated plot were 17 ‒ 23% higher, while the traction power demand values were 9 ‒ 32% lower in comparison with the Neosol treated plot in the first and the second year of the study, respectively. We assume the cumulative positive effect of soil conditioning on the physical soil properties in the study area, therefore the long-term application of Neosol is recommended for farms having similar soil properties.